'In the name of the children': mixed couples' parenting analysed through their naming practices. Issue 1 (2nd January 2019) - Cerchiaro, Francesco
ABSTRACT: This work draws on the life stories of 18 couples, of which the men, married to Italian women, come from majority-Muslim countries. These couples incorporate more layers of differences: religious, as the two partners are socialised into both Islam and Catholicism, and racial-ethnic, as a white Italian partner is married to a non-white immigrant partner. Partners' narratives are analysed according to the naming practices they adopt. Although mixed marriages are interpreted as a gradual loosening of traditional ties, naming practices show how their choices are connected with couples' racial, ethnic and faith backgrounds, the expectations of the family of origin and the social context. Three naming processes are identified: double names to signal a 'pact of equity' between parents' cultural heritages, alternation of names to reflect the couple's 'mutual migration' over time and names which transmit minority ethnic and religious identities. The conclusions note how naming choices highlight different parenting strategies in dealing with pluralism in everyday family life.